The Continuing Non-Criminalization of Marital Rape in India: A Critical Analysis - Kadyan, Sneha (Women & criminal justice, 2025)
India remains one of 36 countries that have not criminalized marital rape. Following an outline of the issue, we examine reasons that allow for the continuing non-recognition of the offense through an exception to the statute on rape in the Indian Penal Code. We do so through an intersecting analysis of the status of women in economic, socio-cultural and political domains. As India is a patriarchal society, women lack power and voice in the familial space. This leads to normalization of violence as well as non-consensual sex within marriage. The inconsistencies and misconceptions in judicial understanding of the issue are examined by scrutinizing landmark judgements, extreme cases, and, statements for and against criminalizing marital rape. We discuss the implications of the current non-recognition of marital rape and conclude by outlining how legal change may occur.